Healing the healers: Unlocking psychological well-being through meaningful work and quality of work life - Aprilia, Eka D.; Adam, Muhammad; Zulkarnain, Zulkarnain; Mawarpury, Marty (Narra J, 2025)
Healthcare workers in developing countries, such as Indonesia, experience significant psychological stress due to heavy workloads, limited resources, and systemic inefficiencies, all of which negatively impact their psychological well-being (PWB). The aim of this study was to investigate the direct and indirect effects of quality of work life (QWL) on PWB, with meaningful work (MW) as a mediating variable. A cross-sectional survey was conducted with 285 healthcare professionals from various healthcare facilities, including specialists, general practitioners, and nurses. Data were collected using validated scales to assess QWL, MW, and PWB. Pearson correlation analysis was employed to examine relationships among variables, while mediation analysis tested direct and indirect effects. The results indicate that QWL positively influences PWB both directly (β=0.22, p<0.001) and indirectly through MW (β=0.13, p<0.001). Furthermore, MW was found to be a strong mediator (β=0.61, p<0.001), underscoring its critical role in enhancing purpose and resilience. Specialists reported the highest QWL and PWB, whereas nurses exhibited the lowest levels, highlighting occupational disparities. These findings suggest that enhancing the QWL and fostering MW can significantly improve healthcare professionals' PWB. Accordingly, organizations should prioritize strategies that promote MW and improve work-life conditions to support mental well-being and job satisfaction.